Content analysis of fisheries vis-a-vis agriculture and animal husbandry based (Krishidarshan) live-phone-in television programmes in West Bengal - Ghosh, Amitava; Sharma, Arpita (Indian Journal of Fisheries, 2014)
Content analysis is a research method that uses a set of procedures to make valid inferences from text. This is used extensively in media communication. Krishidarshan is an agriculture based television show of Doordarshan, with various segments including live-phone-in programmes. A study was carried out to perform content analysis of live-phone-in television programmes of Krishidarshan in West Bengal from 2007-2012. For this, secondary data was accessed from telecast register of Krishidarshan, Doordarshan Kendra Kolkata. Sector specific classification namely agriculture, animal husbandry and fisheries, was done. Experts’ involvement from different organisations was also recorded. Appropriate descriptive statistics and parametric tests were used. It was found that majority of programmes were related to agriculture (86.98%) followed by animal husbandry (7.37%) and fisheries (5.65%). Results of analysis of variance revealed significant difference between number of programmes under each sector. Under agriculture related topics, programmes on agriculture schemes were highest with 9.04% and for animal husbandry, programmes related to poultry and duck farming were highest with 26.67%. In case of fisheries, topics related to fish health and pond management were highest (43.8%). Majority of experts were from Department of Agriculture in case of agriculture based programmes and from State Agriculture Universities for animal husbandry and fisheries.